Unraveling intestinal microbiota’s dominance in polycystic ovary syndrome pathogenesis over vaginal microbiota - Yu, Xia; Li, XiaoQin; Yang, Hui (Frontiers in Cellular and Infection Microbiology, 2024)
Background Polycystic ovary syndrome (PCOS) is a prevalent endocrine disease in women, intricately linked to hormonal imbalances. The microbiota composition plays a pivotal role in influencing hormonal levels within the body. In this study, we utilized a murine model to investigate how intestinal and vaginal microbiota interact with hormones in the development of PCOS. Methods Twenty female mice were randomly assigned to the normal group (N) and the model group (P), where the latter received daily subcutaneous injections of 0.1 mL DHEA (6 mg/100 g). Throughout the experiment, we evaluated the PCOS mouse model by estrus cycle, serum total testosterone (T), prolactin (PRL) and luteinizing hormone (LH) levels, and ovarian pathological morphology. The microbial composition in both intestinal content and vaginal microbiota were studied by 16S rRNA gene high-throughput sequencing. Results Compared with the N group, the P group showed significant increases in body weight, T, and PRL, with significant decrease in LH. Ovaries exhibited polycystic changes, and the estrous cycle was disrupted. The intestinal microbiota result shows that Chao1, ACE, Shannon and Simpson indexes were decreased, Desulfobacterota and Acidobacteriota were increased, and Muribaculaceae, Limosilactobacillus and Lactobacillus were decreased in the P group. T was significantly positively correlated with Enterorhabdus, and LH was significantly positively correlated with Lactobacillus. The analysis of vaginal microbiota revealed no significant changes in Chao1, ACE, Shannon, and Simpson indices. However, there were increased in Firmicutes, Bacteroidota, Actinobacteriota, Streptococcus, and Muribaculaceae. Particularly, Rodentibacter displayed a robust negative correlation with other components of the vaginal microbiota. Conclusion Therefore, the response of the intestinal microbiota to PCOS is more significant than that of the vaginal microbiota. The intestinal microbiota is likely involved in the development of PCOS through its participation in hormonal regulation.